A micro-Raman study of Cu-particulate-filled epoxy matrix composites - S. Tognana; W. Salgueiro; M. B. Valcarce (eXPRESS Polymer Letters)
A micro-Raman study is carried out to investigate the influence of the filler on the curing process of bisphenol A diglycidyl ether (DGEBA)-based epoxy matrix composites. The composites are cured (14 h at 393 K) with an anhydride (methyl tetrahydro phthalic anhydride, MTHPA, 100:90 pbw), catalyzed with a tertiary amine (0.7 pbw) and filled with a 30% volume of Cu particles of approximately 75 µm in diameter. The experimental results are compared with those obtained for the same epoxy resin unfilled and for the same composite with Cu filler but not catalyzed. The micro-Raman experimental technique is used to search for information on the curing process in different regions of the matrix, near to and far from the copper filler, taking into account the results of differential-scanning-calorimetry measurements performed on the same composites. The results provide information on the influence of the copper filler on the curing process of the epoxy matrix. Differences were observed in the peaks associated with the epoxy ring and the ester group as a function of the distance to the nearest copper particle, but no differences were observed between the different composites.